THEODORE BOONE : The Activist - Grisham, John, author 333699 (London : Hodder & Stoughton, 2013)
Though he's only thirteen, Theodore Boone has spent more time in the courtroom than almost anywhere else, and there's always a new adventure waiting. After having been falsely accused of vandalism and theft, Theo is happy to finally be out of the hot seat, once more dispensing legal advice to friends and community members, when an exciting new case demands his urgent attention.